2016
DOI: 10.1177/0954406215598801
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the power draw of tumbling mills in wet grinding

Abstract: In comminution, mill power plays a major role from the economics standpoint and is a critical design criterion. It is influenced by a range of parameters such as media charge level (ball filling), slurry filling, slurry concentration and mill speed. In this work, the effects of these operating parameters were investigated using a pilot mill (1000 × 500 mm). To this end, a copper ore (−1000 µm) was used to prepare the slurry. The tests covered a range of slurry filling (U) from 0 to 1.7 with media charge betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The applied relative parameters (2) to ( 15) are dynamic criteria for the similarity of loading movement and grinding process in a tumbling mill by impact action. The values of the dynamic parameters according to the expressions (3), ( 5), ( 9), (13), and (15) make it possible to numerically evaluate the changes in the technological effect of the shock action of loading depending on the initial characteristics of the grinding process.…”
Section: Results Of Analytical Modeling Of Impact Interaction Of Intr...mentioning
confidence: 99%
See 1 more Smart Citation
“…The applied relative parameters (2) to ( 15) are dynamic criteria for the similarity of loading movement and grinding process in a tumbling mill by impact action. The values of the dynamic parameters according to the expressions (3), ( 5), ( 9), (13), and (15) make it possible to numerically evaluate the changes in the technological effect of the shock action of loading depending on the initial characteristics of the grinding process.…”
Section: Results Of Analytical Modeling Of Impact Interaction Of Intr...mentioning
confidence: 99%
“…The high energy intensity of grinding is caused by energy dissipation due to the shear circulation of internal mill loading [2,[8][9][10]. The estimate of the consumed power can be considered as an indirect indicator of the mill's productivity [11][12][13]. Therefore, the problem of reducing the energy intensity of work processes of tumbling mills remains relevant [14].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that with an increase in slurry content, the impact action of the fill decreases because of damping the interaction of grinding bodies. The influence of material content on the power of the mill drive during wet grinding of copper ore was studied in [24]. Slurry concentration was 40, 50, 60, 70, and 80 %.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…It was found that a significant decrease in κ increases magnitude and frequency of impacts and productivity of the grinding process. Effect of values of the chamber filling degree κ = 0.12, 0.18, 0.24, 0.3 and 0.36 on the tumbling mill drive power during wet grinding of copper ore was experimentally studied in [28]. A significant increase in power was observed with an increase in κ.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%